Synthesis, Characterization, Crystal Structure and Free Radical Scavenging Activities of 2-(2-Benzylamine)-6-[(2-benzylamine)amino]-5-nitro-1H-benzo[de]-isoquinoline-1,3(2H)-dione - Zhang, Ye; Qin, Wen; Liao, Yongzhi; Yi, Xianghui (Asian Journal of Chemistry, 2014)
2-(2-Benzylamine)-6-[(2-benzylamine)amino]-5-nitro-1H-benzo[de]-isoquinoline-1,3(2H)-dione (BBNID, 3) was synthesized and then characterized by FT-IR, NMR and elemental analysis. The crystal structure of BBNID was investigated using X-ray diffraction and SHELXTL97 software and the result indicated that BBNID crystallized in the monoclinic system, space group C2/c with a = 8.8032 (14), b = 8.822 (2), c = 13.994 (4) Å, V = 1005.9 (4) Å3; Z = 2. The free radical scavenging activity screening results showed that BBNID exhibited better scavenging activity than the commercial antioxidant BHT against 2,2-diphenyl-1-picrylhydrazyl radical (DPPH•), with IC50 of 43.10 μM.